(untitled) (Indian Journal of Public Health Research & Development, 2020)
Kanchipuram, one of the holiest cities is highly polluted with heavy metals due to industrialization and urbanization. It is most important to know the role of plants in the cleansing process of heavy metals in this temple city. In this study, the heavy metals (Fe2+, Pb2+, Cu2+, Zn2+, Al2+, Cd2+, As2+, Cr3+, Mn2+) from the dust deposited on the leaves of the trees were analyzed. The tree species were collected from different zones of the Kanchipuram town such as residential area, traffic area, Institutional area, hospital area and industrial area. Heavy metals concentrations were analyzed by inductively coupled plasma mass spectrometry. Most of the heavy metals were found below their detectable limits (Pb2+, Cd2+, Cu2+, Cr3+, and As2+). Some of the heavy metals were in highly increased values (Fe2+, Al2+) almost in selected species. In few locations the content of As2+ and Mn2+ in lower levels were deposited on some species. The results obtained from the analysis were compared statistically and correlated by using Pearson’s co-efficient. The results obtained from the analysis shown that the heavy metals were emitted from various combustion processes and other anthropogenic activities. The tree species selected can be used in bio monitoring as bio indicators of increased Fe2+, Al2+ in the ambient air.